Social Protection in Developing Countries: Legal, Economic, and Social Trends - Nodira Rustamova; Sardorbek Sharifzoda; Xurshida Burxanxodjaeva; Lola Rahimqulova; Mukhammad Turdialiev; Farrukh Nurullaev; Dauletbike Eshchanova (Qubahan Academic Journal)
This paper investigates the evolution of social protection frameworks in developing countries, distinguishing between contributory and tax-financed systems. Through a comparative analysis of social insurance, social assistance, public works, and community-based employment programs, this study assesses their effectiveness in mitigating poverty, managing risks, and fostering resilience. A unique aspect of this research lies in its integration of economic, historical, and cultural factors, offering a comprehensive evaluation of social protection beyond conventional economic assessments. Key findings reveal the critical balance between efficiency and equity in resource allocation, underscoring the importance of addressing dependency and compliance in policy execution. By presenting a nuanced framework that bridges technical and social dimensions, this paper contributes to the growing discourse on sustainable social policies in the context of developing nations. It provides policymakers with actionable insights for crafting inclusive, long-term social protection strategies that align with both immediate relief and sustainable development goals.